Economic Volatility and Returns to Education in Venezuela: 1992-2002 - Patrinos, Harry Anthony; Sakellariou, Chris (World Bank, Washington, D.C., 2013)
Preliminary evidence suggests that the rates of return to education in Venezuela have been declining since the 1970s. The authors rigorously estimate the returns to education in Venezuela for the period 1992-2002, and link them to earlier available estimates from the 1980s. They use consistent cross-sections from the "Encuesta de Hogares por Muestreo" (Household Survey) to document falling returns to schooling, and educational levels until the mid-1990s, followed by increased returns thereafter. The authors use quantile regression analysis to provide further insight into and within skill group changes in returns over time.